Critically Hematological Ill Patients Antimicrobial Stewardship (C.H.I.P.S) in intensive care unit: a global cross-sectional survey—an international research project within the Nine-i investigators network - Sarda, Cristina; Tabah, Alexis; Mokart, Djamel; Alp, Emine; Arvaniti, Kostoula; Akova, Murat; Rello, Jordi (Journal of Emergency and Critical Care Medicine, 2019)
Background: Critically Hematological Ill Patients Antimicrobial Stewardship (C.H.I.P.S) is a global cross-sectional survey will describe the most clinical relevant bacteria and antimicrobial pattern of resistance among hematological patients admitted to intensive care units (ICU). At the same time, a global expert challenges on infection control and treatment will be provided. Methods: A global survey will be performed using an electronic platform (SurveyMonkey®). The survey will compile data on key aspects of the current treatment of antimicrobial-resistant bacteria infections among hematological patients admitted in ICU worldwide. All responses to survey questions will be presented as summary statistics and reporting proportions. Statistical analysis by Chi-square test or Fisher’s exact test will be performed to evaluate potential associations. Discussion: Efforts on the development of recommendations and antimicrobial stewardship (AMS) programs focused on critical hematological patients should be directed in the near future. Prevention strategies, type and, timing of antimicrobial therapy, de-escalation (ADE) approach have to be tailored to these patients.